Clinical epidemiology and impact of Haemophilus influenzae airway infections in adults with cystic fibrosis - R. Benson Weyant; Barbara J. Waddell; Nicole Acosta; Conrad Izydorczyk; John M. Conly; Deirdre L. Church; Michael G. Surette; Harvey R. Rabin; Christina S. Thornton; Michael D. Parkins (BMC Infectious Diseases)
Abstract Background Haemophilus influenzae is prevalent within the airways of persons with cystic fibrosis (pwCF). H. influenzae is often associated with pulmonary exacerbations (PEx) in pediatric cohorts, but in adults, studies have yielded conflicting reports around the impact(s) on clinical outcomes such as lung function decline. Accordingly, we sought to discern the prevalence, natural history, and clinical impact of H. influenzae in adult pwCF. Methods This single-centre retrospective cohort study reviewed all adult pwCF with H. influenzae sputum cultures between 2002 and 2016. From this cohort, persistently infected subjects (defined as: ≥2 samples with the same pulsotype and > 50% sputum culture-positive for H. influenzae in each year) were matched (1:2) to controls without H. influenzae. Demographic and clinical status (baseline health or during periods of PEx) were obtained at each visit that H. influenzae was cultured. Yearly biobank isolates were typed using pulsed-field gel electrophoresis (PFGE) to assess relatedness. Results Over the study period, 30% (n = 70/240) of pwCF were culture positive for H. influenzae, of which 38 (54%) were culture-positive on multiple occasions and 12 (17%) had persistent infection. One hundred and thirty-seven isolates underwent PFGE, with 94 unique pulsotypes identified. Two (1.5%) were serotype f with the rest non-typeable (98.5%). H. influenzae isolation was associated with an increased risk of PEx (RR = 1.61 [1.14–2.27], p = 0.006), however, this association was lost when we excluded those who irregularly produced sputum (i.e. only during a PEx). Annual lung function decline did not differ across cohorts. Conclusions Isolation of H. influenzae was common amongst adult pwCF but often transient. H. influenzae infection was not associated with acute PEx or chronic lung function decline.